Segmentation of Images from Fourier Spectral Data (Communications in Computational Physics, 2018)
This paper designs a segmentation method for an image based on its Fourierspectral data. An edge map is generated directly from the Fourier coefficients withoutfirst reconstructing the image in pixelated form. Consequently the internal boundariesof the edge map are not blurred by any (filtered) Fourier reconstruction. The edge mapis then processed with an edge linking segmentation algorithm. We include examplesfrom magnetic resonance imaging (MRI). Our results illustrate some potential benefitsof using high order methods in imaging.